Targeting Pyroptotic Cell Death Pathways in Retinal Disease - Zhao, Mary; Li, Siqi; Matsubara, Joanne A. (Frontiers in Medicine, 2022)
Pyroptosis is a gasdermin-mediated, pro-inflammatory form of cell death distinct from apoptosis. In recent years, increasing attention has shifted towards pyroptosis as more studies demonstrate its involvement in diverse inflammatory disease states, including retinal diseases. This review discusses how currently known pyroptotic cell death pathways have been implicated in models of age-related macular degeneration, diabetic retinopathy, and glaucoma. We also identify potential future therapeutic strategies for these retinopathies that target drivers of pyroptotic cell death. Presently, the drivers of pyroptosis that have been studied the most in retinal cells are the nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, caspase-1, and gasdermin D (GSDMD). Targeting these proteins may help us develop new drug therapies, or supplement existing therapies, in the treatment of retinal diseases. As novel mechanisms of pyroptosis come to light, including those involving other inflammatory caspases and members of the gasdermin protein family, more targets for pyroptosis-mediated therapies in retinal disease can be explored.